The Impact of E-Commerce on Consumer Behavior in the Retail Sector in Saudi Arabia (International Journal of Financial, Administrative and Economic Sciences, 2024)
E-commerce in Saudi Arabia is experiencing rapid growth, driven by technological advancements and government initiatives aligned with Vision 2030. This research aims to understand the impact of e-commerce on consumer behavior in the retail sector by examining factors influencing e-commerce adoption, the challenges consumers face, and how digital transformations affect traditional businesses. The study gathered data from consumer surveys, government reports, and previous studies, using analytical models to understand the relationships between variables and their impact on consumer behavior. Survey results revealed that e-commerce has significantly changed purchasing habits among Saudis, with many preferring online shopping due to convenience and a wide range of options. The key drivers for e-commerce adoption include convenience, time savings, and product variety, while economic factors like competitive pricing play a significant role in attracting consumers. Trust and security in e-commerce platforms are critical, as consumers seek assurance regarding the protection of their financial information and product quality. Consumers face challenges such as product description accuracy, return difficulties, and concerns about data privacy. Digital transformation pressures traditional businesses to adopt digital strategies to remain competitive. Small businesses face difficulties adapting but show potential for innovation through partnerships with major e-commerce platforms. Data shows a remarkable increase in e-commerce revenue in Saudi Arabia from SAR 38.8 billion in 2020 to SAR 204 billion in 2024, with the number of stores rising from 28,676 to 57,000 during the same period. To sustain this growth, companies need to invest in long-term strategies and diversify revenue streams. The Saudi government plays a crucial role in supporting this sector by improving digital infrastructure, enhancing cybersecurity, and supporting startups. By adopting these recommendations, the online shopping experience can be improved, ensuring customer satisfaction and the continued growth of this vital sector.
Keywords: E-commerce; Consumer Behavior; Retail Sector